Proteomic and functional analyses reveal pleiotropic action of the anti-tumoral compound NBDHEX in Giardia duodenalis. Issue 2 (August 2017) - Camerini, Serena; Bocedi, Alessio; Cecchetti, Serena; Casella, Marialuisa; Carbo, Miriam; Morea, Veronica; Pozio, Edoardo; Ricci, Giorgio; Lalle, Marco
Abstract: Giardiasis, a parasitic diarrheal disease caused by Giardia duodenalis, affects one billion people worldwide. Treatment relies only on a restricted armamentarium of drugs. The disease burden and the increase in treatment failure highlight the need for novel, safe and well characterized drug options. The antitumoral compound NBDHEX is effective in vitro against Giardia trophozoites and inhibits glycerol-3-phosphate dehydrogenase. Aim of this work was to search for additional NBDHEX protein targets. The intrinsic NBDHEX fluorescence was exploited in a proteomic analysis to select and detect modified proteins in drug treated Giardia . In silico structural analysis, intracellular localization and functional assays were further performed to evaluate drug effects on the identified targets. A small subset of Giardia proteins was covalently bound to the drug at specific cysteine residues. These proteins include metabolic enzymes, e.g. thioredoxin reductase (gTrxR), as well as elongation factor 1B-γ (gEF1Bγ), and structural proteins, e.g. α-tubulin. We showed that NBDHEX in vitro binds to recombinant gEF1Bγ and gTrxR, but only the last one could nitroreduce NBDHEX leading to drug modification of gTrxR catalytic cysteines, with concomitant disulphide reductase activity inhibition and NADPH oxidase activity upsurge. Our results indicate that NBDHEX reacts with multiple targets whose roles and/or functions are specifically hampered. In addition, NBDHEX is in turn converted to reactive intermediates extending its toxicity. The described NBDHEX pleiotropic action accounts for its antigiardial activity and encourages the use of this drug as a promising alternative for the future treatment of giardiasis. Graphical abstract: